Peningkatan Pemahaman Konsep Lingkungan Bersih dengan Media Animasi Interaktif di Kelas 1 SDN Sawentar 02 Kabupaten Blitar - Eny Rosidah (Civiliza Publishing, 2021)
Abstract. The formation of students' abilities in schools is influenced by the learning process they take. The learning process will be formed based on the views and understanding of the teacher about the characteristics of students and also the nature of learning. To support this, it is necessary for teachers to understand the characteristics of students and their learning process, especially in lower grade elementary schools. Especially in today's learning where learning is used online. At SD Negeri Sawentar 02, Blitar Regency, learning in grade 1 still produces scores that are less than the KKM. It can be seen that of the 20 students who achieved completeness only 8 students or 40%, while the KKM in grade 1 was 70 or 70%. In accordance with this, the teacher conducts classroom action research using interactive animation media.